Indigenizing Colonial Knowledge: The Formation of Pan- Malay Identity in British Malaya - Naoki, Soda (2008)
The current study divides the process of the indigenization of colonial knowledge in identity formation into two aspects, namely transmission and appropriation. The first process lies in the process in which new apprehensions of a colonial society were transplanted from "British" colonizers to "Malays".' The second aspect is the stage in which Malays themselves reorganized their acquired knowledge and made use of it for their own sake.